Hydrocortisone to Improve Survival Without Bronchopulmonary Dysplasia. Issue 3 (24th September 2022) - Watterberg, K.L.; Walsh, M.C.; Li, L.; Chawla, S.; D'Angio, C.T.; Goldberg, R.N.; Hintz, S.R.; Laughon, M.M.; Yoder, B.A.; Kennedy, K.A.; McDavid, G.E.; Backstrom-Lacy, C.; et al.
Abstract : ( N Engl J Med . 2022;386:1121–1131) The diagnosis of bronchopulmonary dysplasia (BPD) in extremely preterm infants portends potentially abnormal growth, neurodevelopment, and respiratory function. This prevalent condition affects half of extreme preterm birth survivors and likely has a multiplicity of causes: prematurity, oxygen exposure, mechanical ventilation, and inflammatory processes. Dexamethasone was previously widely used until adverse neurological effects including cerebral palsy and cognitive impairment became apparent in the patient population later in life. Despite these complications, many extremely premature infants continue to receive dexamethasone therapy for BPD. Hydrocortisone, another steroid, when administered to extremely premature neonates has produced advantageous characteristics and has shown promising test results in neonates who are developing BPD. Administration of hydrocortisone showed mitigating effects on neonatal inflammation and decreased adverse neurodevelopmental effects. This extended trial, beginning in 2011, investigates the efficacy of high-dose hydrocortisone treatment at improving life expectancy without BPD by monitoring for severe neurodevelopmental disorder through 22 to 26 months.